Develop risk assessment and preparedness/ biosecurity plans to limit entry of seed borne diseases of phytosanitary importance - Onaga, G. (2024)
Developing and implementing biosecurity plans is the most effective way to protect against exotic pests and diseases. Biosecurity involves the proactive measures taken to prevent and manage pests and diseases that have not yet entered a country or a region but are anticipated to do so, whether through seasonal patterns or natural means such as seed importation, trade, or wind dispersal. A Biosecurity Preparedness Plan (BPP) plays a crucial role in managing the risk and impact of the introduction or spread of new pests that pose biosecurity risks. BPPs are important to ensure that NPPOs effectively minimize the biosecurity risks associated with international exchange of rice germplasm, which is crucial for germplasm improvement and food security. AfricaRice conducted workshops in partnership with NPPOs from Cote d’Ivoire and Uganda to ensure that both countries develop BPPs effectively to reduce the biosecurity risks linked to the international exchange of rice germplasm. The initial workshop focused on formulating practical strategies for addressing biosecurity risks linked to the importation of rice germplasm. The emphasis was on showcasing key updates in phytosanitary laws and regulations, pinpointing priority pests and diseases linked to rice, detailing detection and diagnosis techniques, evaluating control and eradication strategies, and deliberating on effective awareness and communication strategies, alongside pertinent policies and standards for the countries involved. A biosecurity preparedness evaluation questionnaire was also developed as part of it. The second workshop focussed on formulating preliminary rice biosecurity plans for the importation of rice germplasm into Uganda and Ivory Coast. The Uganda workshop achieved its intended outcomes in 2024. The Cote d’Ivoire workshop did not; however, there are plans to organize it in 2025.